Perencanaan Strategi Marketing Menggunakan Analisis SWOT: Studi Kasus Brothers Barbershop di Purwokerto - Muhamad Wahyu Arifudin; Imam Nur Vausi; Raka Athallah Putra (CV ODIS, 2023)
Brothers Barbershop Purwokerto, a hair-cutting service company with 5 years of operation, faces challenges in a competitive and dynamic industry. To sustain and grow in the market, an effective marketing strategy is crucial. This study develops a marketing strategy plan using SWOT analysis, IFAS, and EFAS analysis to determine the strategic positioning. The marketing strategy is planned using the SWOT matrix based on information gathered through observation, interviews, and literature study. The competitive position of Brothers Barbershop Purwokerto lies in Quadrant I with coordinates (2.73; 2.58), indicating an aggressive position. This signifies the company's strength in facing significant challenges. The recommended strategy is a growth strategy, leveraging and further improving advantageous internal conditions to maintain a strong position